Use of genetic algorithms for the optimum selection of the fenestration openings in buildings - Kalogirou, Soteris A. (My University, 2007)
The objective of this work is to find the optimum window- to-wall area ratio that minimizes the energy cost for cooling, heating and daylighting. Both heating and cooling load are affected by the U-value and the solar heat gain coefficient (SHGC) of the glass whereas the amount of daylighting is affected by the coefficient of visual transmittance of the glass. For this purpose a genetic algorithm is used which is an optimum search technique based on the concepts of natural selection and survival of the fittest. In this work the genetic algorithm seeks to find a solution which minimizes the energy cost. The method is presented for three different types of fenestration with single glass, double glass and double glass for which the outer glass is reflective. A room with one external 10m2 double-brick wall is considered which is the usual case and size for an office room. This is the wall which carries the fenestration and the exercise was performed individually for the four cardinal directions using the weather conditions of Nicosia Cyprus. The results show that for all types of glasses considered the maximum optimum window-to-wall area ratio (WWR) is for the north direction, followed by the west direction whereas the smallest WWR should be in the east direction.
Keywords: Genetic algorithms; Energy cost; Cooling